The tumor marker Fascin is strongly induced by the Tax oncoprotein of HTLV-1 through NF-κB signals - Kreß, Andrea; Kalmer, Martina; Rowan, Aileen G.; Grassmann, Ralph; Fleckenstein, Bernhard (Blood, 2011)
Oncogenic transformation of CD4+ T cells by human T-cell lymphotropic virus type 1 (HTLV-1) is understood as the initial step to adult T-cell leukemia/lymphoma, a process that is mainly initiated by perturbation of cellular signaling by the viral Tax oncoprotein, a potent transcriptional regulator. In search of novel biomarkers with relevance to oncogenesis, we identified the tumor marker and actin-bundling protein Fascin (FSCN1) to be specifically and strongly up-regulated in both HTLV-1 - transformed and adult T-cell leukemia/lymphoma patient-derived CD4+ T cells. Fascin is important for migration and metastasis in various types of cancer. Here we report that a direct link can exist between a single viral oncoprotein and Fascin expression, as the viral oncoprotein Tax was sufficient to induce high levels of Fascin. Nuclear factor-κB signals were important for Tax-mediated transcriptional regulation of Fascin in T cells. This suggests that Fascin up-regulation by Tax contributes to the development of HTLV-1 - associated pathogenesis. © 2011 by The American Society of Hematology.
Created from Fastlane, Scopus look-up